2021
DOI: 10.1038/s41746-021-00391-x
|View full text |Cite|
|
Sign up to set email alerts
|

A novel digital approach to describe real world outcomes among patients with constipation

Abstract: Understanding day-to-day variations in symptoms and medication management can be important in describing patient centered outcomes for people with constipation. Patient Generated Health Data (PGHD) from digital devices is a potential solution, but its utility as a tool for describing experiences of people with frequent constipation is unknown. We conducted a virtual, 16-week prospective study of individuals with frequent constipation from an online wellness platform that connects mobile consumer digital device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Reference [75] is a non-PD digital approach to evaluating constipation via the FitBit monitoring device through which several health bio-markers were gathered, and regression models were used to assess activity on days with constipation and without. The study was a 16-week program with 1540 participants.…”
Section: B R0-2: Wearable Technology For Early Detection and Manageme...mentioning
confidence: 99%
“…Reference [75] is a non-PD digital approach to evaluating constipation via the FitBit monitoring device through which several health bio-markers were gathered, and regression models were used to assess activity on days with constipation and without. The study was a 16-week program with 1540 participants.…”
Section: B R0-2: Wearable Technology For Early Detection and Manageme...mentioning
confidence: 99%
“…Health technology innovations are transforming the discovery, development, and delivery of health products and services 1 4 and significantly changing the way health conditions are diagnosed, treated, and prevented 5 , 6 . These innovations are building a sustainable foundation for affordable, accessible, and high-quality medicines, vaccines, medical devices, and system innovations, pursuing novel solutions, entrepreneurial ventures, and public sector efforts to the most challenging health problems 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Prior literature has demonstrated that constipation may be associated with poorer sleep continuity. Constipation was linked to difficulty falling asleep, 12 changes in total sleep time, [13][14][15][16] and overall reduced sleep quality 17 (Table 1). However, these observational studies, except for one, 16 relied on subjective questionnaires to assess sleep continuity in constipated patients.…”
Section: Introductionmentioning
confidence: 99%
“…Constipation was linked to difficulty falling asleep, 12 changes in total sleep time, [13][14][15][16] and overall reduced sleep quality 17 (Table 1). However, these observational studies, except for one, 16 relied on subjective questionnaires to assess sleep continuity in constipated patients. Past studies have also indicated that constipation may be linked with insomnia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation